(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the results of the experimental research of the peculiarities of the prosodic organization of English television commercials addressed to the recipients with medium social status. It describes the variant realizations of the analyzed texts. A special tribute is paid to the invariant of the intonation model of television commercials as well as to the relevant changes of prosodic parameters stipulated by the function of the texts.